Traditional and local communities as key actors to identify climate-related disaster impacts: a citizen science approach in Southeast Brazilian coastal areas - Pereira, Rafael Damasceno; Brazílio, Lucas de Paula; Trejo-Rangel, Miguel Angel; Duarte dos Santos, Maurício; Silva, Letícia Milene Bezerra; Souza, Lilian Fraciele; Barbosa, Ana Carolina Santana; de Oliveira, Mario Ricardo; dos Santos, Ronaldo; Sato, Danilo Pereira; Iwama, Allan Yu (Frontiers in Climate, 2023)
The impacts of climate-related disasters can be estimated by climate models. However, climate models are frequently downscaled to specific settings to facilitate Disaster Risk Management (DRM) to better understand local impacts and avoid overlooking uncertainties. Several studies (David-Chavez and Gavin, 2018; Cains and Henshel, 2019; Reyes-García et al., 2019; Savo et al., 2016; Kronik and Verner, 2010; Iwama et al., 2021) have registered the increasing importance of recognizing traditional knowledge, co-design, and collaboration with local communities in developing DRM strategies. The objective of this research was co-design local-scale observations with traditional and local communities to characterize their local context regarding the impacts of climate-related disasters. The citizen science approach coupled with participatory action research was conducted with two traditional communities in the Southeast of the Brazilian coast: Quilombo do Campinho da Independência in Paraty, Rio de Janeiro, and the Caiçara (artisanal fishing) community of Ubatumirim in Ubatuba, São Paulo. Working groups were organized with leaders to become community researchers, conducting interviews and actively mobilizing their communities. A structured questionnaire was developed, adapting 22 variables taken from the Protocol for the Collection of Cross-Cultural Comparative Data on Local Indicators of Climate Change Impacts – LICCI Protocol (Reyes-García et al., 2020). A total of 366 impacts were analyzed, after combining the georeferencing form data collected – Survey123 (280 impacts) and the interviews with community leaders (86 impacts). The results showed a significant level of cohesion (α=0.01) between the Caiçara (artisanal fishers) and Quilombola (Afro-descendants) perceptions of climate-related events associated with their subsistence practices and climate variability. These findings highlighting the importance of DRM proposals that recognize traditional peoples and local communities as frontline vulnerable populations while acknowledging their role as key actors in identifying impacts, collecting data on land use and territory, subsistence-oriented activities, and cosmovision. However, it is still necessary to address climate change challenges at different scales. To do this, it is crucial to promote cognitive justice though the recognition of the values of the memories, perceptions and local knowledge, by scaling up locally-driven observations that empower local communities to lead their own climate adaptation efforts.